2006
DOI: 10.1128/jvi.80.7.3675-3678.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mutation Rates of Human Influenza A and B Viruses

Abstract: Human influenza A viruses evolve more rapidly than influenza B viruses. To clarify the cause of this difference, we have evaluated the mutation rate of the nonstructural gene as revealed by the genetic diversity observed during the growth of individual plaques in MDCK cells. Six plaques were studied, representing two strains each of type A and B viruses. A total of 813,663 nucleotides were sequenced, giving rates of 2.0 ؋ 10 ؊6 and 0.6 ؋ 10 ؊6 mutations per site per infectious cycle, which, when extended to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
188
5
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 27 publications
7
188
5
5
Order By: Relevance
“…Finally, molecular characterization studies showed that no molecular adaptive changes occurred and almost identical viruses infected humans and swine. There were only minor differences between human and swine pH1N1 isolates, which is likely, given the natural mutation rate of influenza virus both in vitro and in vivo [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, molecular characterization studies showed that no molecular adaptive changes occurred and almost identical viruses infected humans and swine. There were only minor differences between human and swine pH1N1 isolates, which is likely, given the natural mutation rate of influenza virus both in vitro and in vivo [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A virus can mutate at rates of up to 10 3 mutations/site/year (66). While these rates typically result in many mutations, the population sizes of these viruses allow for efficient selection to remove even marginally deleterious changes (49,67). In addition, even synonymous changes in influenza A viruses can have significant fitness effects and likely experience some level of selection (68).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the ability to reconstitute an error-free genome from a selection of miscopied and correctly copied segments -by an assembly checkpoint or by multiplicity reactivation -may provide a way to escape from Muller's ratchet (the irreversible accumulation of deleterious mutations in an asexually reproducing genome; Muller, 1964;Belshaw et al, 2008;Chao et al, 1997;Pressing & Reanney, 1984). The pressure of deleterious mutations is likely to be acute in influenza viruses because their RNA genomes are reproduced with relatively low fidelity and are prone to damage (Nobusawa & Sato, 2006;Suarez et al, 1992) while seasonal genetic bottlenecks periodically reduce the effective population size of the virus (Gog et al, 2003;Rambaut et al, 2008), increasing the importance of genetic drift (Moya et al, 2004). The ability of segmentation to restore a functional influenza A genome EM image of an RNP negatively stained with uranyl acetate.…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 99%